THE EFFECT OF EXPERIENTIAL LEARNING ON ATTITUDES AND INTENTION: AN EXPERIMENTAL DESIGN - Bernardus, Denny; Murwani, Fulgentius Danardana; Aji, Imanuel Deny Krisna; Padmawidjaja, Liestya; Kusumojanto, Djoko Dwi; Wardoyo, Cipto; Jatiperwira, Stefan Yudana (Universitas Brawijaya, Indonesia, 2020)
In this study, we examined the effect of an entrepreneurship program based on experiential learning on attitudes and intentions. We used a quasi-experimental design. Data were collected by questionnaire from a sample of 200 students attending in an entrepreneurship program and another sample of 200 students as a control group. Our results indicate that the entrepreneurship program significantly improved students'innovativeness, entrepreneurial self-efficacy, and entrepreneurial intention. Furthermore, the students in an entrepreneurship program have a higher (average) innovativeness, entrepreneurial selfefficacy, and entrepreneurial intention, at the end of the entrepreneurship program, than a control group of students.